FBXO22, ubiquitination degradation of PHLPP1, ameliorates rotenone induced neurotoxicity by activating AKT pathway. (10th October 2021) - Zheng, Xiuqin; Yu, Suwen; Xue, Yang; Yan, Fuling
Highlights: Reveal the role and related regulatory mechanism of FBXO22 in Parkinson's disease. FBXO22 degraded PHLPP1 by ubiquitination to ameliorate rotenone induced neurotoxicity by activating AKT pathway. Investigated the function of FBXO22/PHLPP1 axis on rotenone. Abstract: Parkinson's disease (PD) is a neurodegenerative disease caused by the lacking of dopaminergic neurons. Many reports have illustrated that rotenone is applied to establish the experimental model of PD, which simulates PD-like symptoms. FBXO22 is a poorly understood protein that may be involved in neurological disorders. However, little is known about FBXO22 in PD. In this study, first, SH-SY5Y cells were treated with rotenone to construct PD model in vitro . It was discovered that the FBXO22 expression was down-regulated following rotenone treatment. Additionally, overexpression of FBXO22 reduced rotenone treatment-mediated cell apoptosis in SH-SY5Y cells. In view of the ubiquitination effect of FBXO22, our study uncovered that FBXO22 bound with and degraded PHLPP1 by ubiquitination. Next, the effects of PHLPP1 on AKT pathway in PD were further explored. It was demonstrated that PHLPP1 inactivated AKT pathway through down-regulating the pAKT/AKT and pmTOR/mTOR levels. Through rescue assays, the results showed that PHLPP1 overexpression partially reversed the reduction of rotenone induced neurotoxicity caused by FBXO22 overexpression. Finally, we found that overexpression of FBXO22 alleviated rotenone-induced PD symptoms in rat model. Moreover, it was discovered that l -dopa treatment could not affect the FBXO22 expression in PD. In conclusion, findings from our work proved that FBXO22 degraded PHLPP1 by ubiquitination to ameliorate rotenone induced neurotoxicity, which attributed to activate AKT pathway. This work suggested that FBXO22 may be an effective biological marker for PD treatment.